An examination of the achievement of the Jesuit Order in South Africa, 1879-1934 - Ryan, Judy Anne (Rhodes University, Faculty of Humanities, Department of History, 1990)
The Society of Jesus, founded in 1540 by St Ignatius of Loyola, dispatched the first group of five priests and three brothers to the Cape in 1875. Their destination was St Aidan's College (1875-1973) in Grahamstown which they would staff. Two of the priests went to Graaff-Reinet where the Society established a mission house and noviciate (1875-1889). On 1 July 1878 the Zambesi Mission was founded with Henry Depelchin as its appointed leader. The Mission was placed under the direct control of the Jesuit General. St Aidan's became the headquarters of the Zambesi Mission and it was hoped that trainees for the Mission would emerge from the College. The first group of missionaries bound for the Zambesi regions left Grahamstown in 1879. Negotiations followed with the Ndebele chiefdom in Bulawayo and stations were established at Tati, Empandeni and Pandamatenga. Unsuccessful probes into Barotseland and Gazaland followed and a decade later the mission to Zambesia was abandoned and the Jesuits returned to the south where there had been further expansion of the Order's activities. Dunbrody (1882-1934), situated on the Sundays River, had been set up as a base for the Zambesi Mission, as an educational centre for Blacks and as a farm. Keilands (1886-1908) was an attempt to establish a missionary base for the extension of activities into the Transkei. Vleischfontein (1884-1894) in the Western Transvaal, was developed as a staging post between Zambesia and the Cape. In 1924 the Order attempted to develop parish work in Claremont, but initially nowhere else. By 1890 the Jesuits were ready to return to Matabeleland and in the post colonial years a string of stations were founded. Partly to conserve its manpower for the Zambesi enterprise and for financial and economic reasons, Graaff-Reinet was abandoned in 1889, followed by Vleischfontein, Keilands, the parish at Claremont, and Dunbrody. By 1934, the terminal point of the thesis, the only Jesuit presence in South Africa was at St Aidan's which was saved from closure by Papal intervention.
Keywords: Jesuits -- South Africa -- History